Diagnostic Nutrient Media for Isolation and Identification of Anthrax Agent - V. A. Govorunova; L. I. Marinin; R. I. Mironova; M. V. Khramov; A. N. Mokrievich; A. M. Baranov (Проблемы особо опасных инфекций, 2012)
Designed is a differential-diagnostic solid nutrient media for isolation and identification of anthrax agent. This media contains: nutrient base (enzymic hydrolysate of fishbone powder), agar-agar, D (+)-sorbite, pH indicator bromthymol blue, and broad-spectrum antibiotic (polymyxin). The media makes it possible to differentiate virulent (capsular) and avirulent (non-capsular) Bacillus anthracis strains, as well as closely related saprophyte microorganisms, depending upon the color and colony morphology.